Estudo dos efeitos induzidos por doses subletais do inseticida agrícola Tiametoxam sobre parâmetros bioquímicos e comportamentais de baratas da espécie Nauphoeta cinerea - Ferreira, Letícia Campos (2023)
Thiamethoxam (TMX) is an agricultural insecticide belonging to the neonicotinoid family. Its mechanism of action lies in the persistent activation of nicotinic acetylcholine receptors (nAChR) in the nervous system of insects. Their persistence in the environment and incorrect use has negatively affected non-target insects such as bees and other pollinators, leading to serious environmental problems. In this study, we set out to identify the neurobehavioral entomotoxic effects induced by sublethal doses of TMX, using cockroaches of the species Nauphoeta cinerea as an experimental model. Behavioral analysis protocols were used (exploratory behavior, forced swimming, grooming and olfactory memory), along with chemical and biochemical analyses of samples from the insects' nervous systems. Preliminary lethality tests showed that the LD50 of TMX was 0. 8µg.g-1. Sublethal doses of TMX 0.00001- 0.01µg g-1 were therefore determined, similar to those found in the environment. Thus, TMX induced a significant decrease in the insects' exploratory behavior at the lowest dose, as well as a reduction in sustained locomotor activity at all doses. In addition, TMX induced a significant increase in leg grooming behavior at all doses. TMX also negatively interfered with the insects' olfactory memory at the lowest dose. Spectroscopic analysis of the essential minerals presents in the brains of Nauphoeta cinerea showed a significant alteration in the homeostasis of these compounds for: S, K, Ca, Ti, Mn, Fe, Cu and Zn. TMX also significantly altered the activation profile of the enzyme Glutathione S-Transferase (GST) at the highest dose. The results of this study show that even at sublethal doses, TMX still induces behaviorally relevant changes in insects. The neurolocomotor and olfactory memory changes observed in cockroaches reinforce the effects observed in other insect models, such as bees. In this sense, our data show that the environmental entotoxic effects of TMX on insects are potentially associated with impaired homeostasis of essential minerals which directly influence central and peripheral neurotransmission. Furthermore, the activity on GST reinforces its critical role in the detoxification of organisms and suggests that it may be a valuable target for the purposeful induction of resistance to neonicotinoid insecticides, offering a possible solution to reduce their adverse environmental impacts.